EXPLORING THE RICH TAPESTRY OF BRITISH TV PROGRAMS - Hayitqulova , Asilaxon; Nurmatova , Umidaxon (Educational Research in Universal Sciences, 2023)
This article explores the diverse and enduring landscape of British TV programs. From historical dramas and quirky comedies to gripping crime series and thought-provoking documentaries, British television has a rich tradition of producing high-quality content that appeals to audiences both in the UK and around the world. The article highlights iconic shows, their global impact, and the ability of British TV to foster cultural exchange. It also discusses the influence of streaming platforms, the role of British talent, and the industry’s contribution to meaningful social discussions.